Efficiency of cotton meal, cashew apple, mango peel and almond incorporation on growth and economic performances of broiler in Côte d’Ivoire - Naka, TOURE; Rokiatou, BAMBA; Noel, YAPI Jean; Thierry, KONE Fankroma Martial (Edelweiss Applied Science and Technology, 2025)
The objective of this study is to evaluate the effectiveness of a partial substitution of corn with local agro-food by-products, particularly cashew apple, mango peel, mango almond, and soybean meal with cotton meal in the ration of broilers during the growth phase. Thus, four rations, including one control and three experimental, were constituted, and each of them was used to feed 180 Cobb 500 strain chicks, each 18 days old. In each of the experimental rations, corn was replaced at a rate of 20% with one of the three by-products, while in each ration, soybean meal was replaced at a rate of 10% with cotton meal. The control group was fed a commercial industrial food. The different batches were raised until the age of 45 days, during which growth indicators, including body weight, daily weight gain, feed conversion ratio, and mortality, were determined. Furthermore, an economic evaluation was carried out to assess the profit margin linked to the use of these local inputs in broiler feed during breeding. The results showed that rations based on local by-products did not degrade the growth performance of broilers and even reduced the cost of production while increasing the farmer’s profit margin during breeding. The study is important because it allows for the valorization of locally available by-products in producer countries as a substitute for imported ingredients. This is an advantage for farmers and poultry producers.